2009
DOI: 10.1308/003588409x359204
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Management of Patients Who Deliberately Self-Harm

Abstract: INTRODUCTION Deliberate self-harm is a common problem that often requires orthopaedic treatment. Patients with injuries due to deliberate self-harm are often referred to our unit. This study assessed the type of treatment required and the cost of treatment. PATIENTS AND METHODS We undertook a retrospective survey of deliberate self-harm patients with known ICD-10 psychiatric disorders admitted for orthopaedic care from a medium-secure, female-only, psychiatric unit. Data were collected on admission rate, durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Differenzierte Analysen zeigen, dass dieselben spezifischen Diagnosen wie bei den Jugendlichen vorlagen. Dennoch trat eine generalisierte Angststörung bei den Jugendlichen viermal so häufig [17,18,21,29,32,33] und eine posttraumatische Belastungsstörung [17,18,21,33,29,34] fast doppelt so häufig auf wie bei Erwachsenen. In einem ähnlichen Größenverhältnis stehen Alkoholmissbrauch und Alkoholabhängigkeitsstörung (2,5-fach höhere Rate bei Jugendlichen) [17,18,21,29,32] und erwartungsgemäß externalisierende Störungen, die primär in der Kindheit und Jugend diagnostiziert werden, bei Erwachsenen und Jugendlichen (3,9-fach höhere Rate bei Jugendlichen).…”
Section: Allgemeine Analyseunclassified
“…Differenzierte Analysen zeigen, dass dieselben spezifischen Diagnosen wie bei den Jugendlichen vorlagen. Dennoch trat eine generalisierte Angststörung bei den Jugendlichen viermal so häufig [17,18,21,29,32,33] und eine posttraumatische Belastungsstörung [17,18,21,33,29,34] fast doppelt so häufig auf wie bei Erwachsenen. In einem ähnlichen Größenverhältnis stehen Alkoholmissbrauch und Alkoholabhängigkeitsstörung (2,5-fach höhere Rate bei Jugendlichen) [17,18,21,29,32] und erwartungsgemäß externalisierende Störungen, die primär in der Kindheit und Jugend diagnostiziert werden, bei Erwachsenen und Jugendlichen (3,9-fach höhere Rate bei Jugendlichen).…”
Section: Allgemeine Analyseunclassified
“…Finally, a self-care "rescue pack" can provide early patientled intervention, by not only preventing cutaneous wound aggravation, but also by empowering patients to sustain their safety [8]. Rescue packs may contain gloves, dressing materials, and a wound-care leaflet that enables patients or guardians to effectively manage wounds by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Meltzer [7] reported that approximately 50% of people with schizophrenia experience self-injury. Additionally, common risk factors associated with self-injurious behaviors include major depressive disorder with psychotic features and manic episode of bipolar I disorder [8]. Although there are various psychological drivers of self-destruction, most forms result in cutaneous wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of self-mutilation and drug use have been reported in patients with severe psychiatric disorders and in incarcerated felons [ 8 – 10 ]. Therefore, self-mutilation should always be considered by emergency room physicians in cases of injuries in patients with unusual behavior and psychiatric disorders as well as incarcerated individuals [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%